Designing a Model for E-Banking Effect on Banking Competitiveness Ability(case study: five Selected banks in Tehran) - Seyed Mohammad Reza Hoseinipour; Mohammad Mahdi Parhizgar; Mirza Hasan Hoseini; Ali Akbar Jowkar Jowkar (پژوهش‌های مدیریت عمومی, 2018)
Abstract The purpose of this study was to design a structural model of the effect of electronic banking on increasing the competitive ability of banks(five selected banks) . The method of research is descriptive survey. A questionnaire was used to collect data. The statistical population consisted of directors, deputies and experts of offices and banks of Tehran (five selected banks). 269 of them  participated in the research. A structural equation model(SEM) by Lisrel software was used to analyze the data. The results showed that culture, perceived security, ease of use, trust, website quality, privacy and innovation have a positive and significant effect on the competitive ability of banks. However, the effect of speed on competitive ability of banks was not significant. Overall, the results of the role of electronic banking on the competitive ability of banks were confirmed. Therefore, it can be concluded that e-banking leads to increase  banks' competitive ability. Introduction  Today, The issue of competition between firms is the subject of discussion among managers,politicians and academics(Peña-Vinces& Urbano,2014). Competitive ability refers to the superior position of a company compared to its competitors in that industry . When a company has more profits than other companies in the same industry , it be known as a company with a competitive advantage in this market(Bleoca,2014) .Without a competitive ability, the company will have little economic justification and will be financially in decline) Kim&Oh,2004 (. There  is Strong competition among commercial banks .It means even Most innovative  products and services are copied by others. Then bank opportunity to protect its competitive ability,will be declined(Al-Alak,2014(.  Electronic Banking is one of main factors that facilitates  banks competitive  ability(Joseph & Stone,2003).   Case study For measuring the variables of the research, 300 questionnaires containing 42 questions were distributed among managers, assistants and experienced experts in the field of E-Banking Tehran city’s selected banks. Materials and Methods  This is a descriptive- correlation study modeled based on structural equations model. Research statistical population included 1000  bank experts in tehran. Research sample of 278 experts  were randomly selected through stratified random sampling method using Cochran formula (1997). Data were collected through questionnaire. Validity of the instrumentations was verified through content validity, and confirmatory factor analysis, as well using SPSS. Once covariance errors were removed and fitness factors were examined, factor analysis was confirmed; further, reliability of research instrumentations was also obtained larger than 0.07 using Cronbach’s alpha test, indicating high validity of the questionnaires. Discussion and Results The purpose of this study was to design a structural model for the effect of electronic banking on increasing the competitive ability of banks. The results of structural equation model showed that technology culture, perceived security, ease of use, trust, web site quality, privacy and service innovation have a positive and significant effect on competitive ability, but the effect of speed on competitive ability is not significant. Also, 70% of the competitive variance is explained by the research model. Conclusion As we observed in this study, the role of electronic banking on the competitive ability of banks were confirmed.Because seven factors of     e-banking have a positive and significant effect on the competitive ability of banks. Therefore, it can be concluded that Electronic banking leads to increase  banks' competitive ability.